Accuracy of STRONGKids to Identify Risk of Children Malnutrition in Sanjiwani General Hospital Gianyar, Bali - Dewa Ngakan Putu Yogi Astika; Putu Triyasa; Rima Kusuma Ningrum (Warmadewa University, 2021)
Malnutrition in the hospital is a condition that needs to be watched out for because it affects the journey and healing process of hospitalized patients. Until now, the prevalence of malnutrition in the hospital is still high in both adult and pediatric patients. Medical usually focuses only on the diagnosis and treatment of the patient. Medical staff rarely pay attention to the nutritional status of patients who are hospitalized so that malnutrition in the hospital often goes undetected. Malnutrition screening is required while the patient will be hospitalized. It is necessary to do research to test the accuracy of STRONGKids as a malnutrition filter test in pediatric patients in hospitals, especially at Sanjiwani General Hospital Gianyar and the percentage of malnutrition in hospitals at Sanjiwani Gianyar Hospital so that they receive early treatment. The purpose of this study was to determine the accuracy of STRONGKids as a screening test for malnutrition in the hospital for children at Sanjiwani General Hospital Gianyar. This research uses design cross sectional by the diagnostic test method. Samples were taken by method consecutive sampling. The number of samples is 40 people. The data analysis technique used the SPSS computer program. STRONGKids data are presented in 2 x 2 table form Chi square. The results obtained were the percentage of hospital malnutrition of 9.8%. STRONGKids with a cutoff value of 1 had a sensitivity of 100% and a specificity of 35.1%. So the STRONGKids score has a fairly high sensitivity. So that the use of the STRONGKids score in combination with anthropometric measurements can be used to detect malnutrition in hospitals. Key words: sensitivity, STRONGKids, child malnutrition in hospital